2008
DOI: 10.1182/blood-2007-05-091769
|View full text |Cite
|
Sign up to set email alerts
|

BCR-ABL1 mediates up-regulation of Fyn in chronic myelogenous leukemia

Abstract: Chronic myelogenous leukemia (CML) in IntroductionThe management of chronic myelogenous leukemia (CML) has been revolutionized by kinase inhibitors that were developed in response to cues from biologic studies of the BCR-ABL1 oncogene. However two challenging problems persist: the progression of the disease to blast crisis and resistance to kinase inhibition. 1 Continued investigation of BCR-ABL1 kinase signaling will provide insight into these problems. Members of the Src kinase family, which regulate prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 15 publications
(15 reference statements)
10
67
2
Order By: Relevance
“…We established here that Fyn is up-regulated in imatinib-and PD166326-resistant K562 cell lines, linking Fyn overexpression to acquisition of resistance to BCR-ABL inhibitors. This is coherent with the fact that resistance to imatinib is a common feature in patients with accelerated phase or blast crisis (12) and with its potential role in transformation (37). The IM-R K562 cells described by Donato et al retained active BCR-ABL kinase activity that was inhibitable by imatinib (21), suggesting that BCR-ABL was not coupled to proliferation or survival of K562-R cells.…”
Section: Molecular Cancer Therapeuticssupporting
confidence: 56%
See 3 more Smart Citations
“…We established here that Fyn is up-regulated in imatinib-and PD166326-resistant K562 cell lines, linking Fyn overexpression to acquisition of resistance to BCR-ABL inhibitors. This is coherent with the fact that resistance to imatinib is a common feature in patients with accelerated phase or blast crisis (12) and with its potential role in transformation (37). The IM-R K562 cells described by Donato et al retained active BCR-ABL kinase activity that was inhibitable by imatinib (21), suggesting that BCR-ABL was not coupled to proliferation or survival of K562-R cells.…”
Section: Molecular Cancer Therapeuticssupporting
confidence: 56%
“…Taken together, our findings are in favor of an important role of Fyn in the resistance to BCR-ABL inhibitors. Ban et al also reported that most of the CML cells from patients in blast crisis were positive for Fyn, whereas the majority of chronic and accelerated specimens were negative (37). Of note, BaF3 cells expressing imatinib point mutants of BCR-ABL retained the ability to up-regulate Fyn (37).…”
Section: Molecular Cancer Therapeuticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fyn inhibition by siRNA induces cell cycle arrest and impairs cell viability and migratory ability Because Fyn is considered an important mediator of mitogenic signaling and a regulator of cell cycle, growth and proliferation (Cowden Dahl et al, 2009;Ban et al, 2008;Posadas et al, 2009), we conducted experiments where Fyn expression was inhibited by siRNA and assessed the effect on proliferation, viability and migration of the cells. Indeed, by using Fyn-siRNA (si-Fyn) we were able to obtain an 80% decrease in the expression of Fyn mRNA (Fig.…”
Section: Resultsmentioning
confidence: 99%